ANALISIS PRAKTIK PEMESANAN PAKAIAN DI GARMEN MA’HAD AL-ZAYTUN MENURUT SAYYID SABIQ - Susanti, Susanti; Rojak Samsudin, Agus; Maulana, Rizal (Cahaya Ilmu Bangsa, 2024)
The aim of this study is to analyze in depth the clothing ordering practices at the Al-Zaytun Garmen, specifically focusing on the contract, product specifications, and payment methods, as well as their compliance with the Istisna' contract principles according to Sayyid Sabiq's perspective. This research employs a descriptive qualitative method with techniques including in-depth interviews, observation, and documentation. The results indicate that the Al-Zaytun Garmen offers two ordering options: individual and mass orders. Regarding the contract aspect, there is clarity between the ordering party and the Garmen regarding transaction terms. Product specifications are also clearly outlined to ensure the final product meets customer requirements. For individual orders, payment methods involve a down payment and settlement upon product pickup, whereas mass orders use a non-cash payment system. From Sayyid Sabiq's perspective, this practice generally aligns with the principles of the Istisna' contract, particularly in terms of mutual consent and fair pricing. However, there are challenges in ensuring delivery timelines, which may reduce compliance with Sharia principles. Therefore, it is recommended that Al-Zaytun Garmen implements a digital system for real-time production tracking to ensure delivery timelines and specification compliance. Keywords: Made-to-order sales; Al-Zaytun Garmen; Sayyid Sabiq;